2019
DOI: 10.1177/0361198118823498
|View full text |Cite
|
Sign up to set email alerts
|

The Geography and Equity of Crowdsourced Public Participation for Active Transportation Planning

Abstract: Transportation planners increasingly use new forms of online public participation alongside traditional in-person approaches, including crowdsourcing tools capable of encouraging geographically specific input. Digital involvement may be particularly valuable in exploring methods to plan at a megaregional scale. Research is beginning to address digital inequalities, recognizing that broadband and smartphone access may restrict opportunities for disadvantaged groups. However, the geography and equity of particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To date, few studies have investigated bike-share system ridership in recreation-heavy systems. As such, these operators have needed to rely on qualitative measures and public engagement to help build-out their system (Griffin and Jiao 2018, 2019). Our research intends to fill this gap and focuses on the relationship between built environments and bike-share station usage in cities with small-scale systems and low bicycling-commute-share levels.…”
Section: Bike Sharing and The Surrounding Built Environmentmentioning
confidence: 99%
“…To date, few studies have investigated bike-share system ridership in recreation-heavy systems. As such, these operators have needed to rely on qualitative measures and public engagement to help build-out their system (Griffin and Jiao 2018, 2019). Our research intends to fill this gap and focuses on the relationship between built environments and bike-share station usage in cities with small-scale systems and low bicycling-commute-share levels.…”
Section: Bike Sharing and The Surrounding Built Environmentmentioning
confidence: 99%
“…This study is intended to help transportation planners and policy makers understand socio-demographic differences and other factors in using active transportation to address equitable transportation. Transportation planners should also engage with online tools as options for public participation ( 86 ). Other studies can focus on identifying the barriers underrepresented populations experience when attempting to use active transportation.…”
Section: Discussionmentioning
confidence: 99%
“…They highlight that 'although crowdsourcing has a lot of potential to efficiently increase participation and could potentially lead to more effective outputs, neither of the two outcomes is guaranteed'. Specifically on the issue of geography and equity, Griffin and Jiao [40] report that 'In some contexts, smartphone applications can help reach lower-income communities, even when compared with in-person meetings' whereas Mihelj et al [41] found that 'Rather than helping increase the diversity of audiences, online access seems to reproduce, if not enlarge, existing inequalities' .…”
Section: Digital Technology For Public Participationmentioning
confidence: 99%